Examining hybrid digital/material resources in networked learning: A critical realist approach - Walker, Steve; Davies, Sarah (Proceedings of the International Conference on Networked Learning, 2014)
'Sociomateriality' refers to a range of perspectives on the problematic relationship between people and technology that has recently gained traction in the learning technology literature. Sociomaterialists typically draw on actor network or agential realist approaches to the understanding of technology. The ways these approaches understand the world, we argue, have limitations and we propose an alternative approach to conceptualising the complex relationship between people, artefacts and organisation drawing on critical realist perspectives on technology. This approach accepts that our understandings of a particular technology are mediated by our theories both of a technology's inherent material and nonmaterial properties and of its social situation. It also recognises that aspects of the natural world are autonomous from our understandings and that these are inherent in our technologies. We suggest a similar autonomy for the underlying mathematics which structure the possibilities of the digital world. Hybrid artefacts are comprised both of a digital component, as is typical of networked learning technologies, but also important and distinctive physically material aspects. Many examples of the remote control of experimental devices can be found in the engineering and science education literatures where physical experimental devices incorporate digital control, sensor and other informational components in physical equipment such as telescopes or nuclear reactors. With the emergence of the 'internet of things' we expect to see increasing experimentation in the use of hybrid technologies in learning contexts. The distinctive materiality of these hybrid devices offers an interesting context in which to develop a theory of the relationship between the social and the material in (learning) technology. We elaborate a framework for thinking about 'hybrid' digital/material artefacts in networked learning drawing on contributions from the critical realist literature and illustrate how this may be used through the example of a remote student experiment to measure biochemical oxygen demand, as part of a practical distance learning Level 2 environmental science module at the Open University. The experiment is a relatively simple example of a remote experiment, requiring students to observe digital pressure sensors on samples of water and wastewater as a measure of biological activity. We conclude with a brief discussion of the strengths and weaknesses of our approach.